Content Analysis of Student Book When English Rings A Bell (Revised Edition) for Grade VIII of Junior High School - Adi, Hayati Wasistyo (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
The aim of this study was to analyze the relevance of the materials with the cognitive and psychomotor domains in the 2013 English curriculum competence in English Rings a Bell textbook for grade eight of junior high school. This study used qualitative methodology. The researcher conducted the analysis of textbook based on theory of Anderson and Krathwohl’s (2001) taxonomy of cognitive domain and Simpson’s (1972) taxonomy of psychomotor domain in order to more focus on it relevancy with materials in the textbook. The instrument used to collect the data were observation in the form of checklists and document analysis. The result showed that in term of cognitive domain, there were 23 materials in the book which were relevant or 74.19%, 7 materials which were partly relevant or 22.58%, and only 1 material which irrelevant or 3.2%. Meanwhile, the in term of psychomotor domain, there were 10 materials in the book which were relevant or 32.25%, 10 materials also which were partly relevant, and 11 materials which were irrelevant or 35.48 %. Thus, it can be concluded that the materials in this textbook materials are relevant with 2013 curriculum, in term of cognitive domain. Even though, it lacks of relevant materials of psychomotor domain. Keywords: textbook analysis; ; ; ;